The Marble Lion from Lion Tumulus near Kerch. to the Question About Sculptures on the Cimmerian Bosporus - Goroncharovskiy, Vladimir (Acta Archaeologica Lodziensia, 2020)
In this article the author presents a very rare find from the 1894 excavations of the so-called Lion Tumulus near Kerch. It is a huge marble statue of a lion, which is shown leaning on the head of a bull supported by its left paw. The Lion Tumulus is dated by an inscription to AD 14/15 and can be classified as a Royal tomb. Perhaps a rival of the Bosporan King Aspurgus in the struggle for the throne was buried there.